THE DEVELOPMENT ANALYSIS OF SOCIAL PARTNERSHIP IN UKRAINE - Vasyliuk, S. V. (Science and Transport Progress, 2007)
Work is devoted to development of social partnership at production level that stabilizations socially of labour relations on the enterprise. Attention is accented on that for dynamic development of social partnership a human capital is a base.